Training trainers of agricultural librarians - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
first course on 'Training of trainers in agricultural information' in collaboration with the Ecole de Bibliothécaires, Archivistes et Documentalistes (EBAD) of the University Cheikh Anta Diop in Dakar, from 17 July to 11 August 1995